1994
DOI: 10.1016/0014-5793(94)01028-5
|View full text |Cite
|
Sign up to set email alerts
|

The protective function of the xanthophyll cycle in photosynthesis

Abstract: The rapid conversion of the carotenoid violaxanthin to zeaxanthin via antheraxanthin (xanthophyll cycle) in potato leaves exposed at 23 ° C to a strong white light of 2000/iE. m -2-s-I was associated with a slight inhibition of photosynthetic electron transport (as estimated from chlorophyll fluorescence measurements) and a low lipid peroxidation (as estimated from ethane measurements). When the xanthophyll cycle was blocked by dithiothreitol (3 mM) or low temperature (3°C), photoinhibition of electron transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…It must be noted, however, that the protective function of the V cycle is probably not restricted to PSII, because the cycle takes place in both PSII and PSI (15). Inhibition of the V cycle by DTT, a potent (though nonspecific) inhibitor of the V deepoxidase, was associated with only a slight increase in the level of PSII photoinhibition in strong light whereas, concomitantly, pronounced lipid peroxidation monitored by the production of ethane was induced (16). This suggests that the V cycle could be involved in a general protection of the photosynthetic apparatus against photooxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted, however, that the protective function of the V cycle is probably not restricted to PSII, because the cycle takes place in both PSII and PSI (15). Inhibition of the V cycle by DTT, a potent (though nonspecific) inhibitor of the V deepoxidase, was associated with only a slight increase in the level of PSII photoinhibition in strong light whereas, concomitantly, pronounced lipid peroxidation monitored by the production of ethane was induced (16). This suggests that the V cycle could be involved in a general protection of the photosynthetic apparatus against photooxidation.…”
mentioning
confidence: 99%
“…In situ decomposition of -3 unsaturated hydroperoxy fatty acids into ethane was accelerated by a brief heat treatment (90 s) of the samples in a microwave oven. After cooling the flask, 1 ml of the gas phase was withdrawn and injected in a gas chromatograph for ethane determination (16).…”
mentioning
confidence: 99%
“…Zeaxanthin synthesis in high light was also found to prevent photooxidative stress and lipid peroxidation (Sarry et al, 1994;Havaux et al, 2000) by a mechanism that seems to be different from NPQ (Havaux and Niyogi, 1999). In a number of cases, accumulation of zeaxanthin was shown to increase tolerance to photooxidative stress while NPQ was not substantially modified (Davison et al, 2002;Havaux et al, 2004;Johnson et al, 2007).…”
mentioning
confidence: 99%
“…Zeaxanthin also appears to have a role in establishing tolerance to photooxidative stress by an NPQ-independent process, which protects the lipids of the thylakoid membrane from oxidative damage (14). Havaux and Niyogi (15) found that the Arabidopsis npq4 mutant, devoid of the PsbS protein, and so lacking the rapidly reversible component of NPQ, was still able to protect itself from lipid peroxidation, whereas the npq1 mutant, lacking a functional violaxanthin de-epoxidase enzyme and so devoid of zeaxanthin, suffered extensive oxidative lipid damage upon exposure to specific conditions of high light and low temperature.…”
mentioning
confidence: 99%